Pengaruh beberapa teknik pengendalian terhadap keragaman dan intensitas berbagai jenis penyakit yang muncul pada pertanaman pepaya di Pekon Way Nipah Kecamatan Pematang Sawa - Firnando Firnando; Radix Suharjo; Joko Prasetyo; Muhammad Nurdin; I Gede Swibawa; Franciscus Xaverius Susilo (Jurnal Proteksi Tanaman Tropis, 2020)
The study was aimed to determine the diseases in papaya plantations and to evaluate the effect of various disease control techniques against the intensity of disease in papaya plants in Pekon Way Nipah, Pematang Sawa District, Lampung. This research was conducted in October 2018 to May 2019 in the Biotechnology Laboratory, Faculty of Agriculture, University of Lampung and in Pekon Way Nipah, Pematang Sawa, Tanggamus, Lampung. This study was randomized block designed (RBD) with eight treatments consisting of control (K), biological spray agent (AHSP), manure plus biological agents (PK + AH), soil biological treatment agent (AHSI), bactericide spray (BSP)), manure (PK), solarization (SL), and tillage (OT). The study showed that the diseases that occurred on papaya plantations were suspected as powdery mildew, brown spots 1, brown spots 2, curly cladosporium, leaf curly, root rot and stem base. The treatment of manure plus biological agents reduced the severity of brown spot 1, brown spot 2, powdery mildew, and cladospsorium curling while solarization treatment suppressed the occurrence of root rot and base stem disease.